Calcite e-twins as a tectonic indicator, paleo stress pattern and structural evolution of the Zagros hinterland, SE Iran - Dorzadeh, Hamed; Shafieibafti, Shahram; Keshavarz, Saeede; Omrani, Jafar; Rashidi, Ahmad; Nemati, Majid; Derakhshani, Reza (Frontiers in Earth Science, 2024)
Through the examination of calcite twins, this research outlines the tectonic development and paleo stress patterns of the Paleozoic Routshon complex situated in the southeastern segment of the Sanandaj-Sirjan zone, a hinterland region of the Zagros orogeny in southeastern Iran. The study of orogenic phase indicates that the deformation event affecting the southern sector of the Sanandaj-Sirjan zone aligns with the Cimmerian orogenic phase of the Late Triassic period. A variety of structural features at both map and outcrop scales highlight the importance of slip partitioning in the structural evolution of this region, driven by inclined transpression. Observations suggest that the deformation related to contractional components includes steeply to moderately plunging folds, dip-slip domain deformation primarily involving thrusts, and ongoing deformation by strikeslip component motion, which results in thrust-related ductile shear zones. The analysis of calcite c-axis fabrics from mylonite samples obtained from these shear zones indicates a low-temperature monoclinic pattern of non-coaxial deformation. This deformation type underscores the impact of the strike-slip component in the development of progressive simple shear within thrust-related shear zones in this segment of the Sanandaj-Sirjan zone. Dynamic analysis of c-axis fabric data reveals a NE-SW orientation for the principal compressive axes (σ1) in this area. This direction, corroborated by additional data such as fault surface, GPS, and earthquake focal mechanism data, confirms that the orientation of the compressive axes (σ1) has remained consistent from the Late Triassic to the present.